Deployment of Artificial Intelligence for Enhancing Monitoring and Evaluation of Schools in Nigeria: Challenges and Solutions - Chinelo, Nwankwo Nkechi; Charles, Udegbe Chigozie (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
The effective monitoring and evaluation (M&E) of schools is a critical component of ensuring quality education, accountability, and optimal resource utilization in Nigeria. Traditional M&E methods have often been constrained by inefficiencies such as delayed data collection, inaccurate reporting, limited analytical capacity, and inadequate coverage of educational institutions, particularly in rural and underserved areas. In recent years, the deployment of Artificial Intelligence (AI) has emerged as a transformative approach to address these limitations, offering the potential to revolutionize how educational data is collected, analyzed, and applied for decision-making. This study examines the prospects, challenges, and policy implications of integrating AI into the M&E processes of Nigerian schools. The prospects of AI include real-time data capture and analysis, improved accuracy and reliability of school information, predictive analytics for proactive planning, personalized interventions for underperforming schools, and enhanced stakeholder engagement through data-driven insights. Despite these opportunities, the deployment of AI in the Nigerian education sector faces significant challenges, including inadequate infrastructure, limited technical expertise, high implementation costs, fragmented data systems, ethical and privacy concerns, and the absence of comprehensive legal and regulatory frameworks. The study underscores the need for robust policies that promote infrastructure development, capacity building, data standardization, ethical governance, and sustainable financing to facilitate effective AI integration. By highlighting both the potential benefits and the constraints, this study provides actionable insights for policymakers, education administrators, and development partners seeking to leverage AI to strengthen school monitoring and evaluation, improve educational outcomes, and enhance accountability in Nigeria’s education system.